Beginning Arduino - McRoberts, Michael; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
In Beginning Arduino, you will learn all about the popular Arduino microcontroller by working your way through an amazing set of 50 cool projects. You'll progress from a complete beginner regarding Arduino programming and electronics knowledge to intermediate skills and the confidence to create your own amazing Arduino projects. Absolutely no experience in programming or electronics required! Rather than requiring you to wade through pages of theory before you start making things, this book has a hands-on approach. You will dive into making projects right from the start, learning how to use various electronic components and how to program the Arduino to control or communicate with those components. Each project is designed to build upon the knowledge learned in earlier projects and to further your knowledge in programming as well as skills with electronics. By the end of the book you will be able create your own projects confidently and with creativity. Please note: the print version of this title is black & white; the eBook is full color. You can download the color diagrams in the book from http://www.apress.com/9781430232407
Light$1 (BEm Up -- LED Effects -- Simple Sounders and Sensors -- Driving a DC Motor -- Binary Counters -- LED Displays -- Liquid Crystal Displays -- Servos -- Steppers and Robots -- Pressure Sensors -- Touch Screens -- Temperature Sensors -- Ultrasonic Rangefinders -- Reading and Writing to an SD Card -- Making an RFID Reader -- Communicating over Ethernet.s
Keywords: Computer science; Computer Science; Computer Science, general